2005
DOI: 10.1210/en.2005-0043
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of the Very Low-Density Lipoprotein (VLDL) Receptors in Streptozotocin-Induced Diabetic Rats: Insulin Dependency of the VLDL Receptor

Abstract: Hyperlipidemia is a common feature of diabetes and is related to cardiovascular disease. The very low-density lipoprotein receptor (VLDL-R) is a member of the low-density lipoprotein receptor (LDL-R) family. It binds and internalizes triglyceride-rich lipoproteins with high specificity. We examined the etiology of hyperlipidemia in the insulin-deficient state. VLDL-R expression in heart and skeletal muscle were measured in rats with streptozotocin (STZ)-induced diabetes. STZ rats showed severe hyperlipidemia o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 41 publications
0
22
1
Order By: Relevance
“…Finally, insulin deficiency stimulates lipolysis in adipose tissue, increasing the delivery of free fatty acid from adipose tissue to liver and consequently, triglyceride production in liver. STZ-induced diabetic rats have shown increased serum triglyceride and free fatty acid levels (29,30). In disagreement, our STZ-induced diabetic rats showed lower serum concentrations of triglyceride and free fatty acid.…”
Section: Discussioncontrasting
confidence: 73%
“…Finally, insulin deficiency stimulates lipolysis in adipose tissue, increasing the delivery of free fatty acid from adipose tissue to liver and consequently, triglyceride production in liver. STZ-induced diabetic rats have shown increased serum triglyceride and free fatty acid levels (29,30). In disagreement, our STZ-induced diabetic rats showed lower serum concentrations of triglyceride and free fatty acid.…”
Section: Discussioncontrasting
confidence: 73%
“…However, mice with STZ induced diabetes and LDL receptor defects often develop severe hyperlipidemia 20, 21. It has also been reported that the severe elevation of serum cholesterol and TG concentrations in STZ-induced diabetic rats 19. And it is a known fact that exaggerated postprandial hypertriglyceridemia is common in diabetic patients and this may also contribute for the development of gastroparesis 5…”
Section: Introductionmentioning
confidence: 99%
“…There is no evidence that the increased heart TG in the setting of diabetes is due to upregulation of lipoprotein receptors. In fact, diabetic hyperlipidemia reduces heart VLDLr protein [ 136 ] due to post-translational regulation. This change may represent a compensatory response that occurs in advanced stages of diabetes aiming to counterbalance cardiac lipid uptake and lipotoxicity that occur in diabetic hearts [ 137 ].…”
Section: Cardiomyopathy In Both Type I and Ii Diabetesmentioning
confidence: 99%